EVALUASI KEBIJAKAN PEMERINTAH TERHADAP PENINGKATAN KUALITAS GURU DAN TENAGA KEPENDIDIKAN DI INDONESIA - Rismiyati, Luthfia Amni; Reannisa, Farraz; Lorenta, Hasianna; Aghnia, Syifa Nur; Suriansyah, Ahmad; Purwanti, Ratna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate various government policies in an effort to improve the quality of teachers and education personnel in Indonesia. Teachers and education personnel are strategic components in the national education system that determine the quality of the learning process in schools. Policies such as teacher certification, Continuing Professional Development (CPD), provision of professional allowances, and recruitment of Government Employees with Work Agreements (PPPK) are the main focus of this study. The method used is a literature review by examining books, scientific journal articles, policy documents, and relevant research findings.The results of the review show that although these policies have been conceptually designed to enhance the competence and welfare of educators, their implementation in the field still faces several challenges. These include training programs that are not contextual, disparities in access across regions, and suboptimal administrative systems. In addition, attention to the role of non-teaching education personnel remains limited, even though they play a vital role in supporting educational success. The uneven implementation of policies across regions also exacerbates disparities in education quality, particularly between developed areas and 3T regions (frontier, outermost, and disadvantaged areas). Based on these findings, the study recommends strengthening regional capacity, designing training based on actual needs, and improving coordination between the central and regional governments. A more adaptive and inclusive policy approach is believed to encourage the achievement of strategic goals in enhancing the overall quality of national education.